PDRB Sektor Pariwisata Terhadap Penyerapan Tenaga Kerja Di Provinsi Jawa Tengah : Analisis Cobb Douglas - Irwan Agus; Indah Purnama Sari (Universitas Indraprasta PGRI, 2021)
This study aims to analyze the influence of the tourism sector's GDP on employment in Central Java Province. The research method uses, Return to Scale Analysis, and Elasticity Analysis on Cobb Douglas Regression. This research data is secondary data in the form of a time series for a period of 15 (fifteen) years, starting from 2005 to 2019, which is represented in semi-annual data. The results show that there is a positive and very significant influence of the tourism sector GRDP variable on the employment of Central Java Province. The GRDP of the Tourism Sector is the dominant variable in increasing the employment of Central Java Province.